A mesterséges intelligencia közigazgatásban való felhasználásával okozott kár (Damages caused by the use of artificial intelligence in public administration) - Tamás Bicskei (KözigazgatásTudomány)
In this paper, I present the relationship between liability for administrative damages and artificial intelligence (AI). It examines the AI systems used in public administration, explores the AI’s legislative and historical background, and describes the related liability issues. It will be concluded that – taking into account the current state of science and the legal environment – the systems currently used in Hungarian public administration cannot yet be considered as autonomous AI, so that in their case there is no relevance for the analysis of liability in comparison with AI. Through the Hungarian legal literature and judicial practice, I will examine how, if “real” AI systems were used in the public administration and the AI Liability Directive were transposed into the Hungarian legal system, the court could use which instrument to examine the existence of liability for damages. Finally, a chatbot providing information to customers within the framework of a customer portal will be analysed. This AI system, in our view, may be capable of causing damage through the exercise of public authority by misrepresentation in the current legal and technological environment.